Severe methotrexate toxicity after treatment for ectopic pregnancy: A case report - YILDIZHAN, BEGÜM; ANIK İLHAN, GÖKÇE; SOYSAL, SUAH (GALENOS YAYINCILIK, 2016)
Severe methotrexate toxicity due to medical treatment of an ectopic pregnancy is presented. The feasibility of low-dose use and success of methotrexate makes it the first drug in the medical treatment of ectopic pregnancies. Besides its advantages, it should be used with caution and severe toxicity should be kept in mind.
Keywords: Methotrexate; pregnancy; ectopic; toxicity; RHEUMATOID-ARTHRITIS; DOSE METHOTREXATE; CAUTIONARY TALE; THERAPY; MANAGEMENT; SINGLE; DRUG